2018
DOI: 10.1016/j.ajpath.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of the Expression of DNA Repair–Related Biomarkers Mediated by Alcohol in Gastric Cancer Patients

Abstract: Alcohol consumption likely induces gastric carcinogenesis through deregulation of RNA polymerase (Pol) III genes and oxidative damage. Transcription factor IIB-related factor 1 (BRF1) overexpression alleviates RNA Pol III transcription inhibition through breast cancer susceptibility gene 1 (BRCA1). Myeloperoxidase (MPO) involvement in cancer is induced by alcohol-mediated oxidative damage. BRCA1/2 and MPO play key roles in DNA repair. BRCA1 and BRCA2 exert different roles in homologous recombination repair. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 33 publications
1
32
0
2
Order By: Relevance
“…It suggests that upregulation of Brf1 and Pol III genes is closely related to liver tumorigenesis. These studies are consistent with recent reports that Brf1 is overexpressed in breast cancer, gastric cancer, and prostate carcinoma [10,38,39].…”
Section: Discussionsupporting
confidence: 93%
“…It suggests that upregulation of Brf1 and Pol III genes is closely related to liver tumorigenesis. These studies are consistent with recent reports that Brf1 is overexpressed in breast cancer, gastric cancer, and prostate carcinoma [10,38,39].…”
Section: Discussionsupporting
confidence: 93%
“…RPS-19, -21, -24 and ribosomal RNA) are upregulated in prostate cancer (PCa) [2,3]. BRF1 expression is elevated and associated with poor prognosis in hepatocellular, breast and gastric cancers [4][5][6] but its role in PCa remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A randomized clinical trial found that drinking could increase serum IL-10 while could decrease serum IL-16, monocyte chemotactic protein-1 and vascular cell adhesion molecule-1 (24). Even alcohol consumption could induce GC tissues expressing high levels of transcription factor IIB-related factor 1 and myeloperoxidase-positive cell infiltration, which were identified as independent prognostic factors for overall survival (25). Thus, championing of temperance in the high incidence area of GC was necessary.…”
Section: Controlsmentioning
confidence: 99%